KOMUNIKASI POLITIK PEMERINTAHAN JOKOWI-JK DALAM PERSPEKTIF MEDIA - Firdaus Muhammad; Andi Fikra Pratiwi (Fakultas Dakwah dan Komunikasi, 2015)
Maneuver President Jokowi invite the opposing faction in Golkar, Bakrie (ARB) and Agung Laksono to the Palace. The same thing, Jokowi invited PPP also hostile camps. Jokowi capabilities reflect the political communication is effective as published in various media. This paper demonstrates how Metro TV and TV One doing the framing of the news. Metro TV tends to support the government, it appears on the selection of a resource that is not balanced, Metro TV tends to continue airing excerpts of an interview of Pranowo Hanung who does not believe will be 100 daily. On television station Metro TV broadcast factual programs exclusive interview with President Joko Widodo. Where the factual program was aired on prime time (primetime) so as to attract the attention of the audience. At one factual programs Metro TV news texts government performance tends to have a duration of more than text news about criticism of the government. Based on this construction Metro TV news does not meet the values of the Islamic concept of journalism. TV One tends to criticize the government, it appears in the narrative reports by news Ancore TV One contains prejudice or find fault with other people or groups exclusive interview along with Vice President Yusuf Kalla, news Ancore questioned the performance of Yusuf Kalla, who is considered likely to be less active when compared to the performance of Yusuf Kalla and Susilo bambang Yudhoyono.